2011
DOI: 10.1055/s-0031-1296332
|View full text |Cite
|
Sign up to set email alerts
|

A sensitive and selective HPLC method for estimation of lamotrigine in human plasma and saliva: application to plasma-saliva correlation in epileptic patients

Abstract: A sensitive and selective high performance liquid chromatographic (HPLC) method was developed and validated for estimation of lamotrigine (CAS 84057-84-1) in human plasma and saliva. The chromatographic separation was achieved with a reversed phase column and a mobile phase consisting of acetonitrile and 20 mM ammonium acetate buffer pH 6.5 (30:70) with a flow rate of 1 mL/min. The calibration curve was linear within the working range for both plasma and saliva. The validated method has been successfully appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…53,122,191,[249][250][251][252] However, it is vital that each and every analytical method is fully validated for use with saliva before application with this biological matrix. These include immunoassays and a range of chromatographic procedures.…”
Section: Analysis Of Aeds In Salivamentioning
confidence: 99%
“…53,122,191,[249][250][251][252] However, it is vital that each and every analytical method is fully validated for use with saliva before application with this biological matrix. These include immunoassays and a range of chromatographic procedures.…”
Section: Analysis Of Aeds In Salivamentioning
confidence: 99%
“…HPLC analysis of plasma and brain tissue samples was performed using an RP-HPLC system (Agilent 1260 Infinity series, Agilent Technologies, Santa Clara, CA, USA) by previously-described methods, 43,44 with some modifications. A C18 reversed-phase analytical column (250 mm ×4.6 mm, ID 5 μm; Agilent, USA) with a C18 guard column (SecurityGuard C18, 4 mm ×3 mm inner diameter (ID); Phenomenex, Torrance, CA, USA) was used for the separation.…”
mentioning
confidence: 99%
“…The authors concluded that, with appropriate timing in sampling, saliva could provide a good alternative for lamotrigine TDM [72]. Incecayir et al also reported a good lamotrigine saliva/serum correlation of r 2 = 0.677, while Mallayasamy et al and Kuczynska et al reported values of r 2 = 0.683 and, respectively, r 2 = 0.82 [70,73,74]. Ryan et al reported good lamotrigine salivary and serum concentrations (r 2 = 0.81-0.84) in both patients under 16 years of age and also adults [75].…”
Section: Lamotriginementioning
confidence: 98%